Technological Change and the Stock Market - Laitner, John; Stolyarov, Dmitriy (American Economic Review, 2003)
Tobin's average q has usually been well above 1, but fell below 1 during 1974 – 1984. Our model explains this pattern and reconciles it with unchanging aggregate investment. The stock market value in the numerator of q reflects ownership of physical capital and knowledge, but the denominator measures just physical capital. Therefore, q is usually above 1. Periodic arrivals of important new technologies, such as the microprocessor in the 1970's, suddenly render old knowledge and capital obsolete, causing the stock market to drop. National accounts measures of physical capital miss this rapid obsolescence. Then q appears to drop below 1.